The need for Africa to develop capacity for vaccinology as a means of curbing antimicrobial resistance - Hope Akegbe; Helen Onyeaka; Ifeanyi Michael Mazi; Opeyemi Alex Olowolafe; Adeola Dolapo Omotosho; Iyiola Olatunji Oladunjoye; Yusuf Amuda Tajudeen; Augustine Seun Ofeh (Vaccine: X, 2023)
The high prevalence of infectious diseases in Africa, combined with weak healthcare systems, poor antimicrobial stewardship, and an unchecked drug supply chain, is steadily reversing the trend in the fight against infectious diseases in this part of the world, posing severe threats to antimicrobial resistance (AMR). AMR continuously evolves and threatens to undermine antimicrobial efficacy and undo advances against infectious diseases. This brewing pandemic is now recognized as a significant worldwide health danger, implicated in several cases of morbidity, mortality, and increasing healthcare costs. Vaccine technology has been proven to be the principal remedy to this imminent danger since it prevents microbial infections. However, since Africa cannot produce its vaccines, it relies on external sources and, as a result, it is significantly affected by vaccine nationalism, hoarding, and instabilities in global supply chains. This has further adversely impacted the ability of African governments to regulate rollouts, protect their citizens, and ultimately rejoin the global economy. This dependency is a severe challenge to Africa's health resilience, as it is unsustainable. Given the inevitability of potential global pandemics and the alarming incidences of multi-drug resistance infections reported daily, Africa must develop the capability to produce its vaccines.The review utilized a systematic search of academic databases and grey literature, as well as a manual search of relevant reports and articles. In this review, we outline the public health threats and concerns that AMR poses to Africans, and the hurdles and advances achieved in vaccine development over the years. We also highlight possible strategies, particularly collaborative efforts, that will accelerate vaccine production and ease the strain of infectious diseases and antimicrobial resistance in Africa. Key findings indicate that Africa has significant gaps in its vaccine manufacturing and distribution capacity, with only a few countries having the ability to produce vaccines. Additionally, existing vaccine production facilities are often outdated and require significant investment to meet international standards. The review also highlights successful initiatives in Africa, such as the mRNA vaccine hub and the African Vaccine Manufacturing Initiative, which have demonstrated the potential for building local vaccine manufacturing capacity. The study concludes that Africa needs to prioritize investment in vaccine research and development, regulatory capacity, and infrastructure to build a sustainable vaccine manufacturing ecosystem.Overall, this review emphasizes the urgent need for Africa to develop its vaccine manufacturing capacity to improve vaccine access and strengthen its ability to respond to future pandemics. The findings underscore the importance of collaboration between African governments, international organizations, and the private sector to build a resilient vaccine ecosystem in Africa.